Exclusive Economic Zone Polluted by Oil Spill; Coastal State Loses - Yulia, Lia; Danial, Danial (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Pollution of the marine environment means the introduction by humans, directly or indirectly, of materials or energy into the marine environment which has an adverse effect on marine biodiversity and marine life. The problem is: the First, how is the responsibility of foreign ship companies due to pollution of the marine environment that occurs in Indonesia's exclusive economic zone in terms of the 1982 United Nations Convention on the Law of the Sea? Second, how is the implementation of the 1982 United Nations Convention on the Law of the Sea towards the responsibility of foreign shipping companies due to pollution of the marine environment that occurs in Indonesia's exclusive economic zone? The method used is normative juridical, with a legal principles approach. while the data analysis is a qualitative juridical analysis, namely analyzing problem identification based on secondary data in the form of primary legal materials, secondary legal materials and tertiary legal materials. The results of this study are: First, the responsibility of foreign ship companies due to pollution of the marine environment that occurs in the Indonesian Exclusive Economic Zone is in the form of compensation for losses incurred; Second, the implementation of the 1982 United Nations Convention On The Law Of The Sea against the liability of Foreign Ship Companies Due to Pollution of the Marine Environment that occurred in the Indonesian Exclusive Economic Zone includes ratification of the 1982 United Nations Convention On The Law Of The Sea and provision of witnesses or compensation to perpetrators pollution.